2015
DOI: 10.1093/jhered/esu087
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Sex Chromosome System in the Knifefish Gymnotus bahianus with Inferences About Chromosomal Evolution of Gymnotidae

Abstract: Cytogenetic studies in Neotropical electric knifefish of genus Gymnotus have shown a remarkable interspecific variability, including distinct sex chromosome systems. In this study, we present the first chromosomal data in Gymnotus bahianus from Contas River basin, northeastern South America. Based on extensive analyses, the modal diploid values were 2n = 36 (30m/sm + 6st) for females and 2n = 37 (32m/sm + 5st) for males. Therefore, a novel XX/XY1Y2 sex chromosome system is described for the genus. Single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In contrast to simple SCSs, where repetitive DNAs play an essential role in sex chromosome differentiation ( Yano et al, 2014 ; Schemberger et al, 2019 ), multiple SCSs appear forced by divergent evolutionary trends. It appears that chromosomal rearrangements are more relevant to the evolutionary process of multiple SCSs than the accumulation of repetitive sequences ( Almeida et al, 2015 ). For this reason, molecular cytogenetic procedures based on fluorescence in situ hybridization (FISH), e.g., using whole chromosome painting (WCP) probes, has been successfully applied in different fish groups, providing new insights into the differentiation of sex chromosomes, especially for multiple ones ( Cioffi et al, 2011 ; Blanco et al, 2014 ; Oliveira et al, 2018 ; Moraes et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to simple SCSs, where repetitive DNAs play an essential role in sex chromosome differentiation ( Yano et al, 2014 ; Schemberger et al, 2019 ), multiple SCSs appear forced by divergent evolutionary trends. It appears that chromosomal rearrangements are more relevant to the evolutionary process of multiple SCSs than the accumulation of repetitive sequences ( Almeida et al, 2015 ). For this reason, molecular cytogenetic procedures based on fluorescence in situ hybridization (FISH), e.g., using whole chromosome painting (WCP) probes, has been successfully applied in different fish groups, providing new insights into the differentiation of sex chromosomes, especially for multiple ones ( Cioffi et al, 2011 ; Blanco et al, 2014 ; Oliveira et al, 2018 ; Moraes et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Including Oplegnathus , about 60 cases of multiple sex chromosomes have so far been reported across the teleost phylogeny (reviewed in [13], for more recent examples, see [30,31,32,33,34,35,36,37,38,39]). In this context, molecular cytogenetics provides a powerful toolbox for understanding the genome evolution and organization [40,41,42], and many of these approaches have enabled unique insights into the vertebrate sex chromosome evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The Gymnotiformes order has considerable variation, not only in diploid number (from 2 n = 24 in Apteronotus albifrons , Howell, 1972 ; Almeida-Toledo et al, 1981 ; Mendes et al, 2012 ; to 2 n = 74 in Rhabdolichops cf eastward , Suárez et al, 2017 ) but also in the karyotype formula and location of repetitive sequences (Fernandes et al, 2005 ; Almeida-Toledo et al, 2007 ; Silva et al, 2009 ; da Silva et al, 2013 ; Jesus et al, 2016 ; Araya-Jaime et al, 2017 ; Batista et al, 2017 ; Sousa et al, 2017 ; Takagui et al, 2017 ). Recently, fluorescence in situ hybridization (FISH), has played an important role in understanding the genome structure of fish species (Yi et al, 2003 ; Cabral-de-Mello and Martins, 2010 ; Martins et al, 2011 ; Vicari et al, 2011 ; Gornung, 2013 ; Knytl et al, 2013 ; Yano et al, 2017 ) and molecular cytogenetic studies in Gymnotiformes have shown dynamic reorganization, including pericentric inversions observed through repetitive DNA position (Fernandes et al, 2017 ), sequence dispersion via transposable elements and the association between different repetitive sequences (Utsunomia et al, 2014 ; da Silva et al, 2016 ; Machado et al, 2017 ) and the presence of different sex chromosome systems (Margarido et al, 2007 ; Henning et al, 2008 , 2011 ; da Silva et al, 2011 , 2014 ; Almeida et al, 2015 ). This evolutionary plasticity of the karyotype is seen in Gymnotus (Table 1 ), a genus that has high interspecific variability in chromosome numbers (Figure 1 , Table 1 ), ranging from 2 n = 34 in Gymnotus capanema (Milhomem et al, 2012a ) to 2 n = 54 in G. carapo (Foresti et al, 1984 ), G. mamiraua (Milhomem et al, 2007 ), G. paraguensis (Margarido et al, 2007 ) and G. inaequilabiatus (Scacchetti et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%